PENERAPAN METODE PROMETHEE UNTUK SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN SERAGAM SEKOLAH PADA KANTOR DESA PALOPO - jorry karim (Universitas PGRI Semarang, 2019)
School uniforms generally are shirts used by students of a school or certain educational institution as the symbol or identity of a school. As the symbol and identity of the school, school uniform must fulfill its conditions, among others: neat and fit in the body, not too loose or tight, not too short, made comfortable so the students are comfortable using it. The most common problem is the process of providing assistance in the village. Many jealousy between the beneficiaries and other poor people. Occasionally the beneficiaries had the same help several times due to incorrect data from the village apparatus. This is due to the current system that has not been computerized at the maximum, still in the form of moving notes from books to Office without any system that helps in decision making. The method used in this decision support system is MCDM MCDM method is one of the most used methods in the area of decision making, the research result shows that the implementation of the decision support system is capable Provides maximum results in decision making and overcoming weaknesses in the old system.